2010
DOI: 10.4314/jasem.v14i3.61462
|View full text |Cite
|
Sign up to set email alerts
|

Residues of Organochlorinated Pesticides in Soil from Tomato Fields, Ngarenanyuki, Tanzania

Abstract: This work presents the concentrations of five pesticide residues, lindane, chlorpyrifos, endosulfan, p, p'-DDE and p, p'-DDD in soil samples collected from tomato fields in Ngarenanyuki, Tanzania. Endosulfan sulphate was detected in 100 % of the sample analysed with mean concentration of 0.2407 mg/kg dw. Chlorpyrifos was detected in 87 % of the samples with mean concentration of 0.1253 mg/kg dw. p, p'-DDE and p, p'-DDD were detected in 46 and 40 % of the samples analysed with mean concentrations of 0.1482 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 8 publications
1
28
0
Order By: Relevance
“…This practice was also reported by Lekei, Ngowi, and London (2014) and Khan, Shabbir, Majid, Naqvi, and Khan (2010) in Arumeru and Pakistan respectively. The practice can cause accumulation of pesticide in soil and water sources as it was detected in a sample of irrigation water in Ngarenanyuki ward in Meru district (Kihampa et al, 2010b). Some pesticides' active ingredients might not be able to decompose in the soils or water hence can be the cause for pesticide residues in tomatoes.…”
Section: Improper Pesticide Disposal Practicesmentioning
confidence: 97%
See 1 more Smart Citation
“…This practice was also reported by Lekei, Ngowi, and London (2014) and Khan, Shabbir, Majid, Naqvi, and Khan (2010) in Arumeru and Pakistan respectively. The practice can cause accumulation of pesticide in soil and water sources as it was detected in a sample of irrigation water in Ngarenanyuki ward in Meru district (Kihampa et al, 2010b). Some pesticides' active ingredients might not be able to decompose in the soils or water hence can be the cause for pesticide residues in tomatoes.…”
Section: Improper Pesticide Disposal Practicesmentioning
confidence: 97%
“…Misuse of these pesticides in vegetable production led to chemical polluting the soil and irrigation water as it was reported in 2010 in Ngarenanyuki and Uwiro estate of Meru district. (Kihampa, Mato, & Mohamed, 2010a, 2010b. Also, improper pesticide application on crops may contribute to accumulation of residues in food materials.…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, in an investigation carried out by Ssebugerea et al (2010) in southwestern Uganda, on monitoring of insecticide residues in soil from Kihiihi sub-county, Kanungu District, organochlorine insecticides were found (non-detectable [ND] to 59 μg kg −1 ) in the analysed samples. A similar study conducted by Kihampa et al (2010) in Tanzania, to assess the level of organochlorine insecticide residues in soil from tomato fields, revealed that DDT metabolites 4,4-DDD and 4,4-DDE were detected in 53 % of the soil samples analysed. A systematic review of studies done in Ghana, a neighbouring country of Togo, to give an integrated picture of agrochemicals, especially exposure of humans, animals, plants, water, soil, sediment and atmosphere, revealed contamination of the Ghanaian environment (Fianko et al 2011).…”
Section: Methodsmentioning
confidence: 83%
“…In Tanzania, pesticide residues were detected in the samples of irrigation water for which frequency of detection was increased for samples collected downstream in the fields as well as in fresh tomatoes (Kihampa et al, 2010b). Despite the established evidence of intensive use of pesticide in tomato production, detectable amount of residues and proven risk of pesticide dietary exposure, there is limited information on the pesticide residual levels from other food products and their associated health risks to consumers in Tanzania.…”
Section: Health Effects Of Pesticidesmentioning
confidence: 99%